INVESTIGATING STUDENTS’ SPEAKING ANXIETY FACTOR IN BILINGUAL PROGRAM AT JUNIOR HIGH SCHOOL STUDENTS - Setyana, Genadea Putri; Budianto, Langgeng; Putera, Alam Aji (English Edu: Journal of English Teaching and Learning, 2022)
Education is an effort to develop human quality; with the development of technology, education develops in the language aspect. English is a popular language today. However, many students still experience speaking anxiety. This research was conducted on bilingual students who focus on two foreign languages. This study aims to find out what are the factors that cause students' speaking anxiety in English. This research uses a descriptive qualitative method with a case study approach. Four students from the bilingual class were taken for interview. This study resulted in the factors causing students' speaking anxiety from embarrassment about negative responses, lack of confidence and lack of preparation, teacher's attitude, and an open evaluation.